Two new species of the genus Mallomonas (Chrysophyceae) from ephemeral pools in the steppe zone of the Southern Urals, Russia - Ignatenko, Marina; Gusev, Evgeniy; Yatsenko-Stepanova, Tatyana (Phytotaxa, 2025)
Two new species, Mallomonas kalmykovae and M. prominentia, are described from small ephemeral pools, located in the steppe zone of the Southern Urals (Russia), based on silica-scale morphology observed using scanning and transmission electron microscopy. Both species belong to section Torquatae, series Mangoferae, and are similar to M. favosa. For M. kalmykovae, characteristic features include oval-rhombic scales, the presence of three longitudinal ribs on the wide arms of the posterior submarginal rib, and 2–3 rows of meshes on the shield arranged in parallel rows along the posterior submarginal rib. Scales of M. prominentia are characterized by the presence of a raised shield, a groove between the shield and the posterior submarginal rib and a wide anterior flange. The shield on the body scales of M. prominentia is raised to a greater extent in the proximal part, forming a protrusion over the posterior submarginal rib.